The Strategy for Development of Heritage Tourism in Singaraja City - Rahmawati, Putu Indah (Universitas Pendidikan Ganesha, 2023)
Tourism potentials have not been fully developed to help increase Buleleng Regency's PAD. Each location must have different strategy tailored to the tourism object manager's strengths, weaknesses, aspirations, and targets. This study aimed to formulate strategy for developing Singaraja city in Bali as a heritage tourism. Data were collected using observation, documentation, and FGD techniques and then analyzed qualitatively. This research found that Singaraja city in the north of Bali has many historical assets of the Buleleng kingdom and buildings during the Dutch colonial period. However, the development of Singaraja city as a heritage destination is challenging. The local government has strong eagerness to introduce these assets into heritage tourism to increase the number of tourists visiting Singaraja city. From this analysis, the tourism development strategies for Singaraja City are: (1) form a professional DMO (Destination Management Organization); (2) the involvement of all tourism stakeholders is vital for the development of the city of Singaraja as an heritage tourism destination; (4) the addition of tourist attractions and facilities to be a priority in the development of heritage tourism in the city of Singaraja; (5) a creative team should be formed immediately to promote the city of Singaraja as an heritage tourist destination.